Statins and postmenopausal breast cancer risk; results from the KARMA cohort - Marie Klintman; Ann H. Rosendahl; Benjamin R. Johannesen; Deirdre Cronin-Fenton; Mikael Eriksson; Kamila Czene; Per Hall; Signe Borgquist (Cancer Causes & Control, 2026)
Purpose To study the incidence and subtype of breast cancer in relation to incident and prevalent statin use in a contemporary Swedish prospective cohort, The Karolinska Mammography Project for Risk Prediction of Breast Cancer, KARMA. Methods A total of 35,315 postmenopausal women attending mammography and included in the KARMA cohort (Jan 2011–March 2013) with data on statin use and potential confounders were studied. During eight years of follow-up, 785 incident invasive breast cancer cases were identified. Results A total of 16% of women were prevalent statin users (prior to study inclusion) and 9% were incident statin users (following study inclusion). In multivariable Cox regression analyses, there was no significant association between incident or prevalent statin use and risk of incident breast cancer (HR adj 1.24, 95% CI 0.89–1.72, and HR adj 0.90, 95% CI 0.73–1.11, respectively). Similarly, no significant association was found for incident or prevalent statin use and subtype-specific risk of breast cancer. Conclusion This prospective population-based study performed in a modern screening population with a substantial number of statin users, concurs with previous publications showing no evidence of an association between statin use and risk of postmenopausal breast cancer.

Meiofaunal diversity across a sharp gradient of fjord oxygenation: Insights from metabarcoding and morphology approaches in foraminifera - Phoebe O'Brien; Magali Schweizer; Filip Morin; Astrid Hylén; Elizabeth K. Robertson; Per O.J. Hall; Sophie Quinchard; Irina Polovodova Asteman (Marine Pollution Bulletin, 2026)

Extraordinary claims require extraordinary evidence: evaluating nodule-associated dark oxygen production - Patrick Downes; Angel Cuesta; Alden Denny; Anders Tengberg; Per O. J. Hall; Lars-Kristian Trellevik; Werner Svellingen; Marcel Jaspars; Alexander P. Webber; Felipe Sales de Freitas; Joaquim P. Bento; Leigh Marsh; et al. (Frontiers in Marine Science, 2025)

Radium isotopes trace cross-shelf nutrient transport in a marginal sea - Aprajita S. Tomer; Tristan McKenzie; Claudia Majtényi-Hill; Tibaud Cardis; Linnea Henriksson; Per O.J. Hall; Beata Szymczycha; Nico Mitschke; Isaac R. Santos (Estuarine, Coastal and Shelf Science, 2025)

Radium isotopes quantify vertical mixing and reveal large benthic silicate fluxes in anoxic deep waters - Tristan McKenzie; Aprajita Singh Tomer; Tibaud Cardis; Claudia Majtényi‐Hill; Beata Szymczycha; Per O. J. Hall; Shibin Zhao; Stefano Bonaglia; Michael Ernst Böttcher; Isaac R. Santos (Limnology and Oceanography, 2025)
Benthic fluxes are important sources of nutrients and dissolved carbon to the water column. Yet, most approaches for quantifying benthic fluxes are labor intensive and cover relatively small areas of the ocean. Here, we use 224 Ra to quantify ecosystem‐scale vertical mixing across a largely hypoxic deep water column in the Baltic Sea and related benthic Si fluxes. Bottom water profiles from 50 stations along a ~ 5000 km cruise track in the Baltic Sea revealed highest 224 Ra activities in the deep anoxic basins near the sediment source. Dissolved Si concentrations reached 110 μ M and followed a similar trend to radium. For the radium‐based vertical mixing model, 26 out of 50 stations satisfied the required assumptions. When criteria were met, the radium profiles resolved vertical mixing rates on the order of 10 −4 m 2 s −1 and median dissolved Si fluxes of 5.9 mmol m −2 day −1 , both well within the range of previous local scale estimates based on modeling and sediment core incubations. Extrapolated benthic dissolved Si fluxes were 32 times greater than river dissolved Si flux to the Baltic Sea, highlighting the large contribution of seafloor sources to the water column.

Higher abundance of adult pike in Baltic Sea coastal areas adjacent to restored wetlands compared to reference bays - Petter Tibblin; Kristofer Bergström; Henrik Flink; Marcus Hall; Hanna Berggren; Oscar Nordahl; Per Larsson (Hydrobiologia, 2023)
The abundance of pike, a keystone top-predator, have declined dramatically in the Baltic Sea since the 1990s likely owing to recruitment failure. It has been proposed that wetland restoration can aid the recovery of the pike stock by increasing the number of recruits produced by anadromous populations. Yet, no previous studies have addressed whether wetland restorations are associated with higher abundances of adult pike in the coastal habitat. To address this, we performed standardised rod-and-reel survey fishing in paired bays with and without wetlands across three coastal areas and 3 years. To estimate dispersal and the contribution of wetland pike to the coastal stock, we tagged captured pike with passive integrated responders (PIT) and employed PIT reader stations in wetland inlets. The results showed that pike abundances were on average 90% higher in bays with an adjacent wetland although the effect varied among areas. Moreover, PIT-data uncovered that wetland pike constituted a high proportion of the pike found in adjacent coastal habitats and that some wetland fish dispersed up to 10 km. These results support that wetland restoration is a valuable tool to aid the coastal pike stock and ultimately restore the function and services of the coastal ecosystem.

Reproductive homing and fine‐scaled genetic structuring of anadromous Baltic Sea perch ( Perca fluviatilis ) - Marcus Hall; Per Koch‐Schmidt; Per Larsson; Petter Tibblin; Yeşerin Yıldırım; Johanna Sunde (Fisheries Management and Ecology, 2022)
To investigate the population dynamics of anadromous Baltic Sea perch Perca fluviatilis (Linnaeus), we studied the migratory behaviour (arrival to spawning location) and population structure (genetic structure and differentiation) of three closely located (

Enhanced benthic nitrous oxide and ammonium production after natural oxygenation of long‐term anoxic sediments - Astrid Hylén; Stefano Bonaglia; Elizabeth Robertson; Ugo Marzocchi; Mikhail Kononets; Per O. J. Hall (Limnology and Oceanography, 2022)
Coastal and shelf sediments are central in the global nitrogen (N) cycle as important sites for the removal of fixed N. However, this ecosystem service can be hampered by ongoing deoxygenation in many coastal areas. Natural reoxygenation could reinstate anoxic sediments as sites where fixed N is removed efficiently. To investigate this further, we studied benthic N cycling in previously long‐term anoxic sediments, following a large intrusion of oxygenated water to the Baltic Sea. During three campaigns in 2016–2018, we measured in situ sediment–water fluxes of ammonium ( ), nitrate ( ), oxygen (O 2 ), dissolved inorganic carbon, and reduction processes using benthic chamber landers. Sediment microprofiles of O 2 , nitrous oxide (N 2 O), and hydrogen sulfide were measured in sediment cores. At a permanently oxic station, denitrification to N 2 was the main reduction process. Benthic N 2 O production appeared to be linked to nitrification, although no net N 2 O fluxes from the sediment were detected. At newly oxygenated sites, dissimilatory reduction to comprised almost half of the total reduction. At these stations, the removal of fixed N was inefficient due to high effluxes of . Sedimentary N 2 O production was associated with incomplete denitrification, accounting for 41–88% of the total denitrification rate. Microprofiling revealed algae aggregates as potential hotspots of seafloor N 2 O production. Our results show that transient oxygenation of euxinic systems initiates benthic reduction, but may not lead to efficient sedimentary removal of fixed N. Instead, recycling of N compounds is promoted, which may accelerate the return to anoxia.

Oxygen‐deficient water zones in the Baltic Sea promote uncharacterized Hg methylating microorganisms in underlying sediments - Eric Capo; Elias Broman; Stefano Bonaglia; Andrea G. Bravo; Stefan Bertilsson; Anne L. Soerensen; Jarone Pinhassi; Daniel Lundin; Moritz Buck; Per O. J. Hall; Francisco J. A. Nascimento; Erik Björn (Limnology and Oceanography, 2022)
Human‐induced expansion of oxygen‐deficient zones can have dramatic impacts on marine systems and its resident biota. One example is the formation of the potent neurotoxic methylmercury (MeHg) that is mediated by microbial methylation of inorganic divalent Hg (Hg II ) under oxygen‐deficient conditions. A negative consequence of the expansion of oxygen‐deficient zones could be an increase in MeHg production due to shifts in microbial communities in favor of microorganisms methylating Hg. There is, however, limited knowledge about Hg‐methylating microbes, i.e., those carrying hgc genes critical for mediating the process, from marine sediments. Here, we aim to study the presence of hgc genes and transcripts in metagenomes and metatranscriptomes from four surface sediments with contrasting concentrations of oxygen and sulfide in the Baltic Sea. We show that potential Hg methylators differed among sediments depending on redox conditions. Sediments with an oxygenated surface featured hgc ‐like genes and transcripts predominantly associated with uncultured Desulfobacterota (OalgD group) and Desulfobacterales (including Desulfobacula sp.) while sediments with a hypoxic‐anoxic surface included hgc ‐carrying Verrucomicrobia, unclassified Desulfobacterales, Desulfatiglandales, and uncharacterized microbes. Our data suggest that the expansion of oxygen‐deficient zones in marine systems may lead to a compositional change of Hg‐methylating microbial groups in the sediments, where Hg methylators whose metabolism and biology have not yet been characterized will be promoted and expand.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Mammographic density as an image-based biomarker of therapy response in neoadjuvant-treated breast cancer patients - Ida Skarping; Daniel Förnvik; Uffe Heide-Jørgensen; Hanna Sartor; Per Hall; Sophia Zackrisson; Signe Borgquist (Cancer Causes & Control, 2021)
Purpose Personalized cancer treatment requires predictive biomarkers, including image-based biomarkers. Breast cancer (BC) patients receiving neoadjuvant chemotherapy (NACT) are in a clinically vulnerable situation with the tumor present. This study investigated whether mammographic density (MD), assessed pre-NACT, is predictive of pathological complete response (pCR). Methods A total of 495 BC patients receiving NACT in Sweden 2005–2019 were included, merged from two different cohorts. Cohort 1 was retrospectively collected ( n = 295) and cohort 2 was prospectively collected ( n = 200). Mammograms were scored for MD pre-NACT according to the Breast Imaging-Reporting and Data System (BI-RADS), 5th Edition. The association between MD and accomplishing pCR post-NACT was analyzed using logistic regression models—for the whole cohort, stratified by menopausal status, and in different St. Gallen surrogate subtypes. Results In comparison to patients with low MD (BI-RADS a), the multivariable-adjusted odds ratio (OR) of accomplishing pCR following NACT was on a descending scale: 0.62 (95% confidence interval (CI) 0.24–1.57), 0.38 (95% CI 0.14–1.02), and 0.32 (95% CI 0.09–1.08) for BI-RADS b, c, and d, respectively. For premenopausal patients selectively, the corresponding point estimates were lower, although wider CIs: 0.31 (95% CI 0.06–1.62), 0.24 (95% CI 0.04–1.27), and 0.13 (95% CI 0.02–0.88). Subgroup analyses based on BC subtypes resulted in imprecise estimates, i.e., wide CIs. Conclusions It seemed as though patients with higher MD at baseline were less likely to reach pCR after NACT—a finding more pronounced in premenopausal women. Larger multicenter studies are needed to enable analyses and interpretation for different BC subtypes.

Decadal shift in foraging strategy of a migratory southern ocean predator - Gideon L. van den Berg; Els Vermeulen; Luciano O. Valenzuela; Martine Bérubé; Andre Ganswindt; Darren R. Gröcke; Grant Hall; Pavel Hulva; Petra Neveceralova; Per J. Palsbøll; Emma L. Carroll (Global Change Biology, 2021)
Rapid anthropogenic environmental change is expected to impact a host of ecological parameters in Southern Ocean ecosystems. Of critical concern are the consequences of these changes on the range of species that show fidelity to migratory destinations, as philopatry is hypothesized to help or hinder adaptation to climate change depending on the circumstances. Many baleen whales show philopatry to feeding grounds and are also capital breeders that meet migratory and reproductive costs through seasonal energy intake. Southern right whales ( Eubalaena australis , SRWs) are capital breeders that have a strong relationship between reproductive output and foraging success. The population dynamics of South Africa's population of SRWs are characterized by two distinct periods: the 1990s, a period of high calving rates; and the late 2010s, a period associated with lowered calving rates. Here we use analyses of stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values from SRW biopsy samples ( n = 122) collected during these two distinct periods to investigate foraging ecology of the South African population of SRWs over a time period coincident with the demographic shift. We show that South African SRWs underwent a dramatic northward shift, and diversification, in foraging strategy from 1990s to 2010s. Bayesian mixing model results suggest that during the 1990s, South African SRWs foraged on prey isotopically similar to South Georgia/Islas Georgias del Sur krill. In contrast, in the 2010s, South African SRWs foraged on prey isotopically consistent with the waters of the Subtropical Convergence, Polar Front and Marion Island. We hypothesize that this shift represents a response to changes in preferred habitat or prey, for example, the decrease in abundance and southward range contraction of Antarctic krill. By linking reproductive decline to changing foraging strategies for the first time in SRWs, we show that altering foraging strategies may not be sufficient to adapt to a changing ocean.

Sulfide oxidation in deep Baltic Sea sediments upon oxygenation and colonization by macrofauna - Stefano Bonaglia; Ugo Marzocchi; Nils Ekeroth; Volker Brüchert; Sven Blomqvist; Per O. J. Hall (Marine Biology, 2019)
Coastal and shelf sediments affected by transient or long-term bottom water anoxia and sulfidic conditions undergo drastic changes in macrofauna communities and abundances. This study investigates how early colonization by two macrofaunal functional traits (epifauna vs. infauna) affects oxygen, sulfide, and pH dynamics in anoxic sediment upon recent bottom water oxygenation. Large mesocosms (area 900 cm 2 ) with 150-m-deep Baltic Sea soft sediments were exposed to three treatments: (1) no animals; (2) addition of 170 polychaetes ( Marenzelleria arctia ); (3) addition of 181 amphipods ( Monoporeia affinis ). Porewater chemistry was investigated repeatedly by microsensor profiling over a period of 65 days. Colonization by macrofauna did not significantly deepen penetration of oxygen compared to the animal-free sediment. Bioturbation by M. affinis increased the volume of the oxidized, sulfide-free sediment by 66% compared to the animal-free control already after 13 days of incubation. By the end of the experiment M. affinis and M. arctia increased the oxidized sediment volume by 87 and 35%, respectively. Higher efficiency of epifaunal amphipods in removing hydrogen sulfide than deep-burrowing polychaetes is likely due to more substantial re-oxidation of manganese and/or nitrogen compounds associated with amphipod mixing activity. Our results thus indicate that early colonization of different functional groups might have important implications for the later colonization by benthic macrofauna, meiofauna and microbial communities that benefit from oxidized and sulfide-free sediments.

A response to “Personalised medicine and population health: breast and ovarian cancer” - Antonis Antoniou; Hoda Anton-Culver; Alexander Borowsky; Mireille Broeders; Jennifer Brooks; Anna Chiarelli; Jocelyne Chiquette; Jack Cuzick; Suzette Delaloge; Peter Devilee; Michael Dorval; Douglas Easton; et al. (Human Genetics, 2019)

Physical activity and mammographic density in an Asian multi-ethnic cohort - Wee Heng Soh; Nadia Rajaram; Shivaani Mariapun; Mikael Eriksson; Farhana Fadzli; Weang Kee Ho; Nur Aishah Mohd Taib; Per Hall; Soo-Hwang Teo (Cancer Causes & Control, 2018)

Transient bottom water oxygenation creates a niche for cable bacteria in long‐term anoxic sediments of the Eastern Gotland Basin - Ugo Marzocchi; Stefano Bonaglia; Sebastiaan van de Velde; Per O. J. Hall; Andreas Schramm; Nils Risgaard‐Petersen; Filip J. R. Meysman (Environmental Microbiology, 2018)
Summary Cable bacteria have been reported in sediments from marine and freshwater locations, but the environmental factors that regulate their growth in natural settings are not well understood. Most prominently, the physiological limit of cable bacteria in terms of oxygen availability remains poorly constrained. In this study, we investigated the presence, activity and diversity of cable bacteria in relation to a natural gradient in bottom water oxygenation in a depth transect of the Eastern Gotland Basin (Baltic Sea). Cable bacteria were identified by FISH at the oxic and transiently oxic sites, but not at the permanently anoxic site. Three species of the candidate genus Electrothrix , i.e. marina , aarhusiensis and communis were found coexisting within one site. The highest filament density (33 m cm −2 ) was associated with a 6.3 mm wide zone depleted in both oxygen and free sulphide, and the presence of an electric field resulting from the electrogenic sulphur oxidizing metabolism of cable bacteria. However, the measured filament densities and metabolic activities remained low overall, suggesting a limited impact of cable bacteria at the basin level. The observed bottom water oxygen levels (

Influence of Natural Oxygenation of Baltic Proper Deep Water on Benthic Recycling and Removal of Phosphorus, Nitrogen, Silicon and Carbon - Per O. J. Hall; Elin Almroth Rosell; Stefano Bonaglia; Andrew W. Dale; Astrid Hylén; Mikhail Kononets; Madeleine Nilsson; Stefan Sommer; Sebastiaan van de Velde; Lena Viktorsson (Frontiers in Marine Science, 2017)

Major Bottom Water Ventilation Events Do Not Significantly Reduce Basin-Wide Benthic N and P Release in the Eastern Gotland Basin (Baltic Sea) - Stefan Sommer; David Clemens; Mustafa Yücel; Olaf Pfannkuche; Per O. J. Hall; Elin Almroth-Rosell; Heide N. Schulz-Vogt; Andrew W. Dale (Frontiers in Marine Science, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

An Experiment with Forced Oxygenation of the Deepwater of the Anoxic By Fjord, Western Sweden - Anders Stigebrandt; Bengt Liljebladh; Loreto de Brabandere; Michael Forth; Åke Granmo; Per Hall; Jonatan Hammar; Daniel Hansson; Mikhail Kononets; Marina Magnusson; Fredrik Norén; Lars Rahm; et al. (Ambio, 2015)

A New Phosphorus Paradigm for the Baltic Proper - Anders Stigebrandt; Lars Rahm; Lena Viktorsson; Malin Ödalen; Per O. J. Hall; Bengt Liljebladh (Ambio, 2014)

Crystalline anatase-rich titanium can reduce adherence of oral streptococci - Marjan Dorkhan; Jan Hall; Per Uvdal; Anders Sandell; Gunnel Svensäter; Julia R. Davies (Biofouling, 2014)

Birth weight, breast cancer susceptibility loci, and breast cancer risk - Rulla M. Tamimi; Pagona Lagiou; Kamila Czene; Jianjun Liu; Anders Ekbom; Chung-Cheng Hsieh; Hans-Olov Adami; Dimitrios Trichopoulos; Per Hall (Cancer Causes & Control, 2010)

Characterizing dispersal patterns in a threatened seabird with limited genetic structure - LAURIE A. HALL; PER J. PALSBØLL; STEVEN R. BEISSINGER; JAMES T. HARVEY; MARTINE BÉRUBÉ; MARTIN G. RAPHAEL; S. KIM NELSON; RICHARD T. GOLIGHTLY; LAURA MCFARLANE‐TRANQUILLA; SCOTT H. NEWMAN; M. ZACHARIAH PEERY (Molecular Ecology, 2009)
Genetic assignment methods provide an appealing approach for characterizing dispersal patterns on ecological time scales, but require sufficient genetic differentiation to accurately identify migrants and a large enough sample size of migrants to, for example, compare dispersal between sexes or age classes. We demonstrate that assignment methods can be rigorously used to characterize dispersal patterns in a marbled murrelet ( Brachyramphus marmoratus ) population from central California that numbers approximately 600 individuals and is only moderately differentiated ( F ST ∼ 0.03) from larger populations to the north. We used coalescent simulations to select a significance level that resulted in a low and approximately equal expected number of type I and II errors and then used this significance level to identify a population of origin for 589 individuals genotyped at 13 microsatellite loci. The proportion of migrants in central California was greatest during winter when 83% of individuals were classified as migrants compared to lower proportions during the breeding (6%) and post‐breeding (8%) seasons. Dispersal was also biased toward young and female individuals, as is typical in birds. Migrants were rarely members of parent‐offspring pairs, suggesting that they contributed few young to the central California population. A greater number of migrants than expected under equilibrium conditions, a lack of individuals with mixed ancestry, and a small number of potential source populations (two), likely allowed us to use assignment methods to rigorously characterize dispersal patterns for a population that was larger and less differentiated than typically thought required for the identification of migrants.

Dissolved organic matter in abyssal sediments: Core recovery artifacts - Per O. J. Hall; Jenny Brunnegård; Gustaf Hulthe; William R. Martin; Henrik Stahl; Anders Tengberg (Limnology and Oceanography, 2007)
We report measurements of pore‐water dissolved organic carbon (DOC), dissolved organic nitrogen, total dissolved carbohydrates, dissolved free monosaccharides, and ammonium in recovered deep‐sea sediments from the Porcupine Abyssal Plain (PAP), Northeast Atlantic. There were distinct maxima close to the sediment‐water interface of these constituents at all times of the year. The very high diffusive effluxes calculated from these porewater distributions were not compatible with simultaneous sediment trap measurements of particulate organic carbon, nitrogen, and carbohydrate fluxes toward the seafloor. Effluxes calculated from pore‐water DOC distributions in recovered cores from another Atlantic deep‐sea site, showing almost identical maxima as those at PAP, were more than an order of magnitude greater than simultaneous in situ chamber DOC flux measurements. We suggest that the dissolved organic matter maxima are predominantly artifacts induced by lysis of, or leakage from, mainly bacterial biomass resulting from decompression and/or warming during recovery of the sediment cores from the abyssal seafloor. Temperature elevation during core recovery from the abyss gives a N 2 saturation of about 150%, and the combined effect of warming and decompression results in a CO 2 saturation of about 135%, which together plausibly are associated with bubble formation creating cell bursting. Previous estimates of microbial biomass in abyssal sediments may be underestimates because of the difficulty of counting lysed bacterial cells. Since exoenzymes are inducible, previous measurements of their activities in recovered abyssal sediments may be overestimates.

Can we trust cancer information on the Internet? – A comparison of interactive cancer risk sites - Alexandra Ekman; Per Hall; Jan-Eric Litton (Cancer Causes & Control, 2005)

Effects of 20-s and 180-s double poling interval training in cross-country skiers - Johnny E. Nilsson; Hans-Christer Holmberg; Per Tveit; Jostein Halln (European Journal of Applied Physiology, 2004)

An in situ instrument for planar O 2 optode measurements at benthic interfaces - Ronnie N. Glud; Anders Tengberg; Michael Kühl; Per O. J. Hall; Ingo Klimant (Limnology and Oceanography, 2001)
A new in situ instrument for two‐dimensional mapping of oxygen in coastal sediments is presented. The measuring principle is described, and potential mechanical disturbances, solute and particle smearing associated with the measurements, and calibration routines are evaluated. The first in situ measurements obtained in two different benthic communities are presented. In a shallow photosynthetic sediment (1 m of water depth), an extensive horizontal and temporal variation in the O 2 distribution caused by benthic photosynthesis and irrigating fauna was resolved. Repetitive planar optode measurements performed along a transect in central Øresund, Denmark (17 m of water depth) revealed a positive correlation between the apparent O 2 penetration depths (OP) measured with a lateral distance 2 distributions within benthic communities. The instrument can be adapted for use at full ocean depths, e.g., on deep‐sea landers or remote operating vehicles.